Effect of different digestion techniques on elements recoveries for spectroscopic analysis in natural medicinal remedies - Helal Uddin, A.B.M.; Khalid, Reem S.; Abbas, Syed Atif (2015)
Natural products have great importance in various medical applications worldwide. Safety and efficacy issues are vital for insuring public health and long-term success of such products. The existence of potentially toxic metals such as arsenic (As), mercury (Hg), cadmium (Cd) and lead (Pb) in some natural medicinal products are often reported. Thus, accurate determination of such metals is required. In general spectroscopic elemental analysis imposed sample preparation/digestion prior to detection. This preliminary step has a considerable impact on the quality of the analytical result especially for complex matrices like plants and herbs. The present study aims to evaluate the effect of close vessel/ microwave digestion system and various digestion regents on metals recoveries by comparing different sample preparation procedures to recommend the most reliable method. Three different digestion methods were evaluated for determining As, Hg, Pb and Cd concentrations in herbal matrices. The methods were A, B and C which represented acid digestion with mixture of nitric-hydrochloric acids HNO3 – HCl in a ratio of 1:3 using conventional open vessel heating program, mixture of nitric acids - hydrochloric HNO3 – HCl in a ratio of 1:3 and a mixture of HNO3-H2O2 in a ratio of 4:1 using close vessel microwave digestion respectively. The comparison was conducted using real herbal medicine samples spiked with various concentrations. Heavy metals were detected with graphite furnace atomic absorption spectrometry (GFAAS). The data was statically evaluated using by one way analysis of variance (ANOVA) followed by Tukey HSD post hoc test for multiple comparison using the Statistical Package for the Social Sciences (SPSS). The observed elemental recoveries for methods A, B and C were (77.4, 89, 94.6) for As, (80.4, 89.5, 93.8) for Hg, (79, 89.27, 92.6) for Pb and (84.8, 91.8, 97) for Cd respectively. The results revealed that method C and B had given remarkable changes of recoveries for all analytes in spiked samples. The statistical analysis indicated good recoveries by microwave digestion methods B and C compared to method A as they had given a significant high recoveries (p<0.05) compared to method A. Although method C was obtained higher recoveries no significant effect was observed between method B and C for all analytes. Hence, both methods can be successfully applied to different kind of natural products analysis.